Eicosapentaenoic acid and branched-chain amino acids fortified complete nutrition drink improved muscle strength in older individuals with inadequate protein intake - Khoonin, Watcharapol; Shantavasinkul, Prapimporn Chattranukulchai; Santivarangkna, Chalat; Praengam, Kemika; Trachootham, Dunyaporn (Frontiers in Nutrition, 2023)
Background Elevated inflammation and negative nutritional balance contribute to sarcopenia, a progressive loss of muscle mass, strength, and function. This study investigated the effect of energy supplementation and the combination of anti-inflammatory factor (eicosapentaenoic acid; EPA) and muscle-synthesis promotor (branched-chain amino acids; BCAA) on body composition, muscle, and inflammatory biomarkers in elderly with inadequate protein intake. Methods A randomized blinded placebo-controlled trial was conducted on 84 elderly with inadequate protein intake. The participants were randomly assigned into four groups receiving a complete nutrition drink; (1) control formula, (2) fortified with 2.2 g EPA, (3) with 2.2 g EPA and 5 g BCAA (2:1:1 of Leu: Ile: Val), and (4) with 2.2 g EPA plus 5g BCAA (4:1:1 of Leu: Ile: Val). Each subject consumed two sachets of the drink to gain 500 kcal/day and performed arm muscle exercises for 3 weeks. Body compositions and handgrip strength were measured using BIA and a dynamometer, respectively. Plasma EPA and BCAA levels were determined using LC-MS/MS to ensure compliance. Muscle protein biomarkers including histidine, β-alanine, and carnosine were measured using LC-MS/MS. Serum inflammatory (IL-6) and anti-inflammatory cytokines (IL-10) were measured by using ELISA. Results No symptoms and signs of adverse events were observed. The right arm muscle mass and handgrip strength were significantly increased after consuming a complete nutrition drink fortified with EPA + BCAA 2:1:1 and 4:1:1 of Leu: Ile: Val (p < 0.05 and p < 0.01, respectively. Consistently, consuming such combinatory formula non-significantly elevated carnosine with reduced histidine, and increased IL-10 with decreased IL-6. All relevant intervention groups showed a significant increase in plasma levels of BCAA and EPA. Conclusion Consuming a complete nutrition drink fortified with 2.2g EPA and 5g BCAA 2:1:1 or 4:1:1 of Leu: Ile: Val for 3 weeks may increase right arm muscle mass and strength in elderly with inadequate protein intake. The tendency of increased dipeptide (carnosine)/decreased free amino acid (histidine) suggests a shift toward muscle protein synthesis. The trend of decreased inflammatory/increased anti-inflammatory cytokines suggests an anti-inflammatory effect. Future long-term studies are warranted to confirm the combinatory effect of BCAA and EPA in the prevention of sarcopenia. Clinical trial registration Thailand Clinical Trial Registry No. TCTR20230116005.